AKTIVITAS ANTIBAKTERI SABUN PADAT EKSTRAK KULIT BUAH NANAS (Ananas comosus L.) PADA Escherichia coli - Elly Purwati; Sih Wahyuni Raharjeng (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Pineapple skin is available in abundance, as much as 50-70% of pineapple fruit. However, this fruit peel is simply thrown away as waste, whereas pineapple peel contains many bioactive compounds such as flavonoids, carotenoids, alkaloids, saponins, and vitamin C. These compounds have various properties, one of which functions as an antibacterial. The purpose of this study was to determine the antibacterial activity of solid soap extract from pineapple peel (Ananas comosus L) with a concentration of 1% and 3% on Escherochia coli. The research method was experimental, making solid soap from pineapple peel extract 1% (F1) and 3% (F2). The extraction method was carried out using 70% ethanol solvent maceration and the bacterial inhibition test using disk diffusion. Chloramphenicol as a positive control. In conclusion, solid soap of pineapple peel extract (Ananas comosus L.) concentration of 3% is more effective than 1% in inhibiting Escherichia coli bacteria with an average inhibition zone of 20.5 mm, SPSS One Way Anova data states a value of 0.016 <0.05 which indicates there is a significant difference.